Réponses

  • Utilisateur Brainly
2013-04-19T14:36:09+02:00

1) 3x²+2x√3+1=0

donc (√3x+1)²=0

donc √3x+1=0

donc √3x=-1

donc x=-1/√3

 

2) 2x²-25=0

donc 2x²=25

donc x²=12,5

donc x=-√12,5 ou x=√12,5

 

3) (2x-3)²=(-5x+7)²

donc (2x-3)²-(-5x+7)²=0

donc(2x-3+5x-7)(2x-3-5x+7)=0

donc (7x-10)(-3x+4)=0

donc 7x-10=0 ou -3x+4=0

donc x=10/7 ou x=4/3

 

4) (x²+1)(5-3x)-10x+6x²=0

donc (x²+1)(5-3x)-2x(5-3x)=0

donc (5-3x)(x²+1-2x)=0

donc (5-3x)(x-1)²=0

donc 5-3x=0 ou x-1=0

donc x=5/3 ou x=1

  • Utilisateur Brainly
2013-04-19T15:39:06+02:00

1.

3x²+2x√3+1=0

(√3x+1)²=0

√3x+1=0

√3x=-1

x=-1/√3

 

2.

2x²-25=0

2x²=25

x²=12,5

x=-√12,5

ou x=√12,5

 

3.

(2x-3)²=(-5x+7)²

(2x-3)²-(-5x+7)²=0

(2x-3+5x-7)(2x-3-5x+7)=0

(7x-10)(-3x+4)=0

7x-10=0 ou -3x+4=0

x=10/7

ou x=4/3

 

4.

(x²+1)(5-3x)-10x+6x²=0

(x²+1)(5-3x)-2x(5-3x)=0

(5-3x)(x²+1-2x)=0

(5-3x)(x-1)²=0

5-3x=0 ou x-1=0

x=5/3

ou x=1

 

 voilà... :)